Bony ankylosis adversely affects postoperative hip function in patients with ankylosing spondylitis undergoing total hip arthroplasty: a retrospective cohort study of 319 consecutive patients - Liangliang Li; Jun Fu; Chi Xu; Ming Ni; Wei Chai; Libo Hao; Yonggang Zhou; Jiying Chen (BMC Musculoskeletal Disorders)
Abstract Background This study reports the mid-term outcomes of primary total hip arthroplasty (THA) and investigates the effect of bony ankylosis on postoperative hip function in patients with ankylosing spondylitis (AS). Methods We identified 544 primary THAs performed in 319 consecutive patients with AS (median age, 33 years) from 2012 to 2017. Survivorship of the implants, complications, and patient satisfaction were investigated. Functional outcomes were assessed by the measurement of hip flexion–extension range of motion (ROM), the Harris hip score (HHS), and the Western Ontario and McMaster Universities Arthritis Index (WOMAC). The hips undergoing THA were divided into a bony ankylosis group and a hip stiffness group based on the severity of hip involvement. The postoperative functional results of the two groups at the most recent follow-up were compared. Results Survivorship was 99.8% with a mean follow-up of 7 years (range, 5–9 years). The main complications included dislocation (5 hips, 0.9%), periprosthetic femoral fracture (15 hips, 2.7%), and infection (primary infection in 2 hips and periprosthetic joint infection in 1 hip, 0.6%). The flexion–extension ROM improved significantly with a median of 0° (0 ~ 120°) pre-operatively to 100° (30 ~ 130°) after THA (P < 0.001), and the HHS improved from 37 ± 19 to 90 ± 5 (P < 0.001). Patient satisfaction was self-scored as ‘Very satisfied’ in 278 (87%) of patients. The most common cause of dissatisfaction in the remaining 41 (13%) patients was poor hip flexion function (58.5% of this subset). Postoperative ROM was significantly lower in the bony ankylosis hips (median, 100° bony ankylosis group vs. 110° hip stiffness group). The bony ankylosis group also had lower postoperative HHS (89 ± 5 vs. 92 ± 5) and had significantly higher WOMAC scores (43 ± 20 vs. 31 ± 18) than the hip stiffness group (P < 0.001). Conclusions Excellent mid-term clinical outcomes can be achieved with modern cementless THA in patients with AS. Poor hip flexion function is the main complaint of patients who are dissatisfied with their outcomes. Bony ankylosis has adverse effects on postoperative hip function in patients with AS, suggesting that performing THA before ankylosis occurs can lead to better subjective outcomes and better postoperative hip function. Level of evidence Level III.